Comparative thermo-economic and advanced exergy performance assessment of wind energy for distributed generation in four sites in Nigeria - Chidiebere Diyoke (Center of Biomass & Renewable Energy, Diponegoro University, 2020)
Electricity access and reliability in Nigeria is poor due to obsolete power distribution infrastructure. This could be improved by deploying wind energy resources. The present research assessed the thermo-economic, advanced and extended exergy analysis of deploying wind turbine for distributed generation in four Nigerian locations. The air temperature and wind speed of the sites was used together with Weibull statistical parameters to mathematically model the thermodynamic performance of selected wind turbine for the sites. The results show that the energy and standard exergy efficiency of the sites ranges from 0.16 – 0.44, 0.05 – 0.37, 0.23 –0.39, 0.26 – 0.37 and 0.12 –0.33, 0.04 – 0.25, 0.17 – 0.28, 0.18 – 0.28 respectively for Enugu, Kaduna, Katsina and Jos. The exergy efficiency based on the extended exergy analysis (EEA) approach was found to be much lower than the standard exergy efficiency for all the sites. Based on EEA, Enugu, Kaduna, Katsina and Jos has exergy efficiency of 1.05, 0.73, 2.52 and 3.22 % respectively. Economic performance results showed that Jos is the best site with least monthly average COE value of 0.15 /kWh which compares closely with global average COE value of 0.14 /kWh for households. Katsina and Enugu have a COE value of 0.19 and 0.84 /kWh respectively while Kaduna is the worst in performance with highest COE value of 1.13 /kWh.